Effects of benzilaminopurine and indole-3-acetic acid on In vitro propagation of Gerbera jamesonii Bolus ex Hook cv. Appelbloesem - Barbosa, Márcio H. P; Pasqual, Moacir; Pinto, José E. B. P.; Arello, Eduardo F.; de Barros, Inacio (Pesquisa Agropecuaria Brasileira, 1993)
Gerbera jamesonii Bolus ex Hook is an ornamental species producing flowers that are cut and sold in the market. In vitro multiplication of cv. Appelbloesem was studied, culturing 3-leaves buds in MS medium (Murashige & Skoog 1962) supplernented with adenine sulphate (80 mg/l), tyrosine (100 mg/l), sucrose (3%), difeobacto agar (7.0 g/l) and the growth regulators 6-benzilaminopurine (BAP) (0.0; 1.0; 2.0 and 4.0 mg/l), and indole-3-acetic acid (IAA) (0.0; 0.25; 0.5 and 1.0 mg/l). The evaluation was realized forty days after inoculation, on mean number of new leaves longer than 1 cm in the initial explant. The multiplication rate was higher in 1.0 mg/l of BAP, disregarding the level of IAA. Roots were formed in treatments without BAP.